Sulfur speciation by HPLC-ICPQQQMS in complex human biological samples: taurine and sulfate in human serum and urine - Lajin, Bassam (Anal Bioanal Chem, 2018)
The advent of the triple quadrupole technology to the inductively coupled plasma mass spectrometry (ICPMS) technique has allowed a strong improvement in the accuracy and detection limits of ICPMS for non-metal elements such as sulfur by removing major polyatomic interferences. Up to now, there has been no report utilizing this development for sulfur speciation in complex human biological matrices. In the present report, we show the success of HPLC-ICPQQQMS for the simultaneous determination of two major sulfur metabolites, taurine and sulfate, in human urine and serum, by direct injection without the need for sample clean-up. The optimized chromatographic method was validated, tested for robustness, and applied for investigating the intra-individual variability in taurine urinary excretion in eight healthy volunteers over a period of 8 weeks. The limit of detection and limit of quantification for taurine determination was found to be 0.2 and 0.7 pmol, respectively. The concentrations found in the analyzed group of urine samples (n = 64) had a range, mean, and SD of 0.6–99, 20.4, and 23.2 μg mL(−1) for taurine, and 115–1373, 616, and 259 μg mL(−1) for sulfate. Taurine was found to exhibit a much higher intra-individual variability than sulfate. The developed method can be applied in large-scale epidemiological studies and clinical studies in order to establish the potential cardioprotective effects of taurine. [Figure: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00216-018-1251-z) contains supplementary material, which is available to authorized users.